An Integrated Queue System With Fingerprint Recognition And Scoring Board In Bank - Samuel Sampe Tuah Purba; Beni Satria; Muhammad Rizki Syahputera (Sean Institute, 2024)
This paper described proposes an integrated queue system for banks, combining fingerprint recognition technology with a scoring board. The system aims to enhance customer service efficiency and security while optimizing queue management. By incorporating fingerprint recognition, customers can easily verify their identity without the need for physical documents or cards, streamlining the authentication process. Additionally, the scoring board provides real-time updates on queue status, allowing both customers and bank staff to monitor waiting times and prioritize service accordingly. The integration of these technologies offers a comprehensive solution to improve the overall banking experience, ensuring smoother operations and higher customer satisfaction. Therefore, the aim of this research is to create a school payment system that is packaged electronically by utilizing the internet network and fingerprint identification as the payment medium. This payment system was created by utilizing fingerprint technology that is embedded in each student's cellphone and is integrated with the internet as a data exchange route. The system flow starts from registering your fingerprint via a fingerprint scanner, logging in, topping up your balance, viewing and selecting the payment list, and finally making a payment by authenticating your fingerprint using a fingerprint reader. It is hoped that this research can ease the burden on treasurers and all students in terms of school payments, especially those within the Tanwirul Afkar Islamic Vocational School so that a payment system can be obtained that is faster, more flexible and safer to use.